Synergic optimization of elastic modulus and superconducting properties in graphene@Fe(Se, Te) hybrid materials. (November 2022) - Liu, Jixing; Shao, Botao; Liu, Xueqian; Li, Meng; Sang, Lina; Zhang, Shengnan; Feng, Jianqing; Li, Chengshan; Li, Jianfeng; Zhang, Pingxiang; Dou, Shixue; Zhou, Lian; et al.
Abstract: Our study investigated the feasibility of optimizing elastic modulus and transport performance of superconductors through engineering strategy, which was realized in the graphene incorporated Fe(Se, Te) hybrid materials via spark plasma sintering process. By analyzing the results of microscopic characterization and transport measurement, the correlation between material synthesis technique and superconducting properties was set up. Specifically, the incorporation of graphene could obviously decrease the elastic modulus of Fe(Se, Te), while the utilization of spark plasma sintering evidently enhanced the upper critical field and irreversible filed of samples. This work provided a facile synthesis for mechanical stable hybrid materials, which should inspire the development for high-performance tape or wire superconductors. Graphical Abstract: Image, graphical abstract